Analisis Implementasi E-Office Pada Corporate Secretary Department PT Agrinas Jaladri Nusantara (Persero) - Naiya Cinta Sabrina; Munawaroh Munawaroh; Ferry Setyadi Atmadja (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
Advances in information technology have encouraged organizations, including state-owned enterprises (SOEs), to implement digital administration systems such as E-Office to improve the effectiveness and efficiency of administrative management. This study aims to analyze the implementation of the E-Office system in the Corporate Secretary Department of PT Agrinas Jaladri Nusantara (Persero), focusing on the system workflow, E-Office support in administrative management, and employees' understanding and skills in operating it. This study is based on policy and information system implementation theory, as well as E-Office success indicators that include human resource readiness, information clarity, authority, and supporting facilities. The research method used is a descriptive qualitative approach. Data collection was carried out through observation, in-depth interviews with four informants directly involved in the use of E-Office, and documentation studies. The results of the study show that E-Office has provided positive support in accelerating administrative processes, increasing transparency, and facilitating document tracking. However, its implementation has not been fully optimal due to obstacles in the tiered approval process, technical system constraints, and differences in the level of understanding and skills of employees. Thus, this study concludes that the success of E-Office implementation is not only determined by the system, but also by the readiness of human resources, consistency of procedures, and continuous organizational support.